The Portrayal of Liberal Feminism in the Main Character's Roles in Difret Film - Samria Sunaryo; Nita Valiantien; Eka Sudirman (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research discusses the personality of Meaza and the portrayal of liberalfeminism values in the Difret film. The researchers uses the theory of characterizationtheory by Bogss and Patrie and liberal feminism values by Wollstonecraft, Mill, andTaylor. The researchers uses qualitative research by Tracy and data analysis by Miles,Huberman, and Saldana for the film. The findings of this research showed threeaspects ofliberalfeminism portrayedin thefilm, namely equaleducation, equalliberty, and suffrage. Those aspects are portrayed through the personality of Meazawhen she struggles to help women in Ethiopia get justice by being intelligent to get anequaleducation,hard-workingandindependenttogetequalliberty.Also,care,determined,and braveare included in getting suffrage.